Application of Adaptive Genetic Algorithm and Particle Swarm Optimisation in scheduling of jobs and AS/RS in FMS. (24th October 2008) - Asokan, P.; Jerald, J.; Arunachalam, S.; Page, T.
Flexible Manufacturing Systems (FMS) are advanced production systems used in industries today. In this context, this paper deals with the problem of scheduling of jobs and Automated Storage and Retrieval Systems (AS/RS) assignments in a FMS environment because in some industries they have machines and this kind of AS/RS. Non-traditional optimisation techniques such as Adaptive Genetic Algorithm (AGA) and Particle Swarm Optimisation (PSO) are implemented to get optimal schedules and storage assignments. The objective function minimises the distance travelled by the Storage and Retrieval (S/R) machine. The results are presented and compared.